2018
DOI: 10.1016/j.cct.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The Anorexia Nervosa Genetics Initiative (ANGI): Overview and methods

Abstract: Background: Genetic factors contribute to anorexia nervosa (AN); and the first genome-wide significant locus has been identified. We describe methods and procedures for the Anorexia Nervosa Genetics Initiative (ANGI), an international collaboration designed to rapidly recruit 13,000 individuals with AN as well as ancestrally matched controls. We present sample characteristics and the utility of an online eating disorder diagnostic questionnaire suitable for large-scale genetic and population research. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

7
0

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 33 publications
0
116
0
Order By: Relevance
“…24 ANGI is an international collaboration established between scientists in United States, Australia/New Zealand, Sweden and Denmark to establish a cohort of individual with and without AN. 25 The ANGI participants involved in our study were those recruited in Denmark along with the iPSYCH participants. Hence, they were QCed and genotyped together along with iPSYCH samples.…”
Section: Brief Summary Of the Cohorts Involved In The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…24 ANGI is an international collaboration established between scientists in United States, Australia/New Zealand, Sweden and Denmark to establish a cohort of individual with and without AN. 25 The ANGI participants involved in our study were those recruited in Denmark along with the iPSYCH participants. Hence, they were QCed and genotyped together along with iPSYCH samples.…”
Section: Brief Summary Of the Cohorts Involved In The Studymentioning
confidence: 99%
“…1. Our discovery sample comes from iPSYCH 24 and the Anorexia Nervosa Genetics Initiative (ANGI), 25 large population-based Danish cohorts of individuals with and without psychiatric disorders for whom information on school grades was available through the Danish education register. 26 Using principal component analysis (PCA), we decomposed the school grades in Danish, English and mathematics (six different grades per individual; Methods) into orthogonal principal components (hereafter, E-factors) that captured distinct cognitive domains relating to math and language.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we have no way of estimating response rate, and though the ED100K has been validated for online administration (Thornton et al, 2018), there may be discrepancies between reported diagnoses and those established by a clinician. Though we found no significant relationship between participants' perceptions of the contribution of genetics to the etiology of eating disorders and whether or not they had a family history of an eating disorder, the effect size was small-medium, suggesting that the lack of statistical significance could be due to sample size.…”
Section: Limitationsmentioning
confidence: 99%
“…The study individuals are from iPSYCH 19 and ANGI, 26 population-based Danish case-cohorts recruited through Danish National registers. 40,41 The iPSYCH cohort comprises of individuals diagnosed with at least one of five major psychiatric disorders (ADHD, ASD, MDD, SCZ and BPD ) and a randomly selected controls without any of the five psychiatric disorders.…”
Section: Study Cohortmentioning
confidence: 99%
“…The aim of the current study is to evaluate if the association between EA-PGS and school performance differ between individuals with and without psychiatric disorders. To do this, we studied the association of EA-PGS with school performance in 30,982 individuals from the Danish iPSYCH 25 and ANGI 26 cohorts, 60% of whom were diagnosed with one or more of six major psychiatric disorders-ADHD, ASD, schizophrenia (SCZ), bipolar disorder (BD), major depressive disorder (MDD) and anorexia nervosa (AN). Through an analysis involving the full cohort we first confirmed that EA-PGS strongly associate with school performance.…”
Section: Introductionmentioning
confidence: 99%